Phytotherapeutic antioxidants - Mishra, Tulika; Kondepati, Ananda Kumar; Pasumarthi, Shalini Devaprasad; Chilana, Gurmit Singh; Devabhaktuni, Suresh; Singh, Pratik Kumar (Asian Journal of Medical Sciences, 2020)
Plants have always been an integrated part of human life, whether we discuss about providing food or we about their medicinal value. Ethnomedicines have led to the discovery of many valuable drugs against various diseases. It has been postulated that most of the disease are related to immune system which is affected by imbalance balance between antioxidants and prooxidants or free radicals. Free radicals are the chemical entities capable of independent existence that contain one/more unpaired electrons and can be balanced by antioxidants. Antioxidants maintain the integrity and function of membrane lipids, cellular proteins, and nucleic acids and the control of signal transduction of gene expression in immune cells. For this reason, the immune cells are particularly sensitive to changes in their antioxidant status. Whenever there is imbalance between prooxidant and antioxidants they can lead to many diseases and even ameliorate the severity of disease like Alzheimer, cardiovascular disorder, cancer etc. There are evidences showing usage of plants as a potent source of antioxidants has provided a lot of support in combating various diseases, without any side effect. Various Bioflavonoids, Carotenoids, Hydroxycinnamates etc helps in scavenging the free radicals and thus proved to be immunostimulant. There are various mechanisms through which these Phyto antioxidants assisted against various disease. The present review is an attempt showing the relationship of free radicals with various diseases and immune system and the role of Phyto antioxidants against various health related conditions.